Keteladanan Tokoh Daud Kepada Allah - Juan Andika Manuputty; Litri Yerisa Eribka; Melan Melan; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This journal highlights that Daud shows an example that can be learned from various aspects of his leadership. Daud, as a God-fearing leader, placed God at the center of all his actions. He showed that loyalty and ability were more important than blood relations, and prioritized God's will in choosing leaders. Daud is also a leader who wants to listen, both the voice of God and the aspirations of his subordinates. He was an aspirational leader, stepping down from his throne to listen to the complaints and suggestions of the people. Daud also knew his messenger, the Lord, and knew and understood his people. He always asks God in every action, and does not act arbitrarily according to his own will.